2023
DOI: 10.1177/22779752231163366
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Reaction to COVID-19: A Cross-Sectional Industry Analysis in Frontier Market

Abstract: The effect of COVID-19 on the efficiency of frontier stock markets at the industrial level has received little attention. This study aimed to analyze the Dhaka stock exchange’s immediate market response to the initial COVID-19 announcement at the industry level. An event study approach was used to cross-sectional daily returns of 311 enterprises grouped into seventeen industry groups to determine anomalous returns for a total of 21 trading days divided into seven separate event periods. According to the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 81 publications
(96 reference statements)
1
3
0
Order By: Relevance
“…Therefore, it can be inferred that Taiwanese stock market prices will be inefficient in the late COVID-19 period. This result is similar to those of Chakraborty (2023) and Adnan and Johani (2023), confirming the inefficiency of equity markets such as India and Dhaka during the COVID-19 pandemic.…”
Section: Tree Structure Modelsupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, it can be inferred that Taiwanese stock market prices will be inefficient in the late COVID-19 period. This result is similar to those of Chakraborty (2023) and Adnan and Johani (2023), confirming the inefficiency of equity markets such as India and Dhaka during the COVID-19 pandemic.…”
Section: Tree Structure Modelsupporting
confidence: 81%
“…Chakraborty (2023) found that investors in the Indian stock market made irrational investment decisions during the COVID-19 crisis and that the inefficiency of the market brought instability to the stock market. Adnan and Johani (2023) confirmed the inefficient market activity during the pandemic in the Dhaka securities market over a short period. Under the EMH, past, present, and even future information sets are immediately, adequately, correctly, and effectively reflected in stock prices (Fama, 1970).…”
Section: Literature Reviewmentioning
confidence: 60%
See 2 more Smart Citations